Reversal of PCNA Ubiquitylation by Ubp10 in Saccharomyces cerevisiae - Gallego-Sánchez, Alfonso (Public Library of Science, 2012)

(untitled)
Regulation of PCNA ubiquitylation plays a key role in the tolerance to DNA damage in eukaryotes. Although the evolutionary conserved mechanism of PCNA ubiquitylation is well understood, the deubiquitylation of ubPCNA remains poorly characterized. Here, we show that the histone H2B(K123) ubiquitin protease Ubp10 also deubiquitylates ubPCNA in Saccharomyces cerevisiae. Our results sustain that Ubp10-dependent deubiquitylation of the sliding clamp PCNA normally takes place during S phase, likely in response to the simple presence of ubPCNA. In agreement with this, we show that Ubp10 forms a complex with PCNA in vivo. Interestingly, we also show that deletion of UBP10 alters in different ways the interaction of PCNA with DNA polymerase ζ–associated protein Rev1 and with accessory subunit Rev7. While deletion of UBP10 enhances PCNA–Rev1 interaction, it decreases significantly Rev7 binding to the sliding clamp. Finally, we report that Ubp10 counteracts Rad18 E3-ubiquitin ligase activity on PCNA at lysine 164 in such a manner that deregulation of Ubp10 expression causes tolerance impairment and MMS hypersensitivity.